Degradasi Nilai-nilai Pendidikan Agama Kristen Pada Masa New Normal Akibat Pandemi Covid-19 - Toisuta, Jakson (Jurnal Apokalupsis, 2023)
This text aims to present a theoretical study on Christian Education values rooted in the Bible, currently facing setbacks due to the integration of new normal regulations during the COVID-19 pandemic. The research methodology employs a descriptive qualitative approach, incorporating a literature study with primary sources such as books, the Bible, scientific journals, and internet references for thorough analysis. Additionally, the study includes observations related to phenomena or events. The study concludes that implementing health protocols to prevent the spread of COVID-19 presents challenges to the application of Christian education values. In the new normal, individuals are mandated to maintain distance, wear masks, avoid handshakes, and refrain from corporate worship in churches. However, this practice of social distancing impedes the expression of brotherly love and living in fellowship with church members to embody Christian values, particularly the concept of Koinonia. Consequently, the adoption of the new normal results in a setback in the application of Christian Education values.